Analysis Question of Higher Order Thinking Skills in Class X Biology Textbooks - Maghfira Mutia; Syarifah Widya Ulfa; Siti Maysarah (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2022)
Some of the questions in the textbooks are in accordance with the development of science and the applicable curriculum. However, it is undeniable that quite a lot of textbooks are not suitable and have not shown HOTS-type questions. Moreover, the analysis of questions in biology textbooks based on the type of HOTS is very rarely carried out. To review this, the analysis of questions in textbooks is needed as evaluation material in improving the quality of books used in learning. This study aims toanalyze the content of the Higher Order Thinking Skill category in the Class X Biology textbook which is used by Sri Langkat Private High School in learning and teacher response Biology is related to the problem in the book. This research uses a qualitative descriptive type of research. The instruments used are document analysis sheets with check list marks and teacher response interview instrument sheets. The guidelines used in the analysis of the questions are indicators of the Higher Order Thinking Skill category. The results of the study stated that there were as many as 170 questions classified as HOTS type questions with the percentage of the distribution of analyzing questions (C4) 87.6%, evaluating questions (C5) 9.4%, questions creating 2.9%. The teacher's response stated that the question writing bah wa was in accordance with the indicators contained in the curriculum and after validating the results of the question analysis, the teacher specifically knew the content of the percentage of HOTS question types in the Biology textbook used in learning.